The Semantic Web: ESWC 2023 Satellite Events Hersonissos, Crete, Greece, May 28 - June 1, 2023, Proceedings - Pesquita, Catia; Skaf-Molli, Hala.; Efthymiou, Vasilis; Kirrane, Sabrina; Ngonga, Axel.; Collarana, Diego; Cerqueira, Renato; Alam, Mehwish; Trojahn, Cassia; Hertling, Sven. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the post-conference proceedings of the satellite events held at the 20th Extended Semantic Web Conference, ESWC 2023, held in Hersonissos, Greece, during May 28-June 1, 2023. The 50 full papers included in this book were carefully reviewed and selected from 109 submissions. They were organized in sections as follows: Posters and Demos, Industry, and PhD Symposium.
Summary of Workshops and Tutorials at European Semantic Web Conference 2023 -- Posters and Demos -- Sparnatural: a visual knowledge graph exploration tool -- Integrating Faceted Search with Data Analytic Tools in the User Interface of ParliamentSampo - Parliament of Finland on the Semantic Web -- SHACL-ACL: Access Control with SHACL -- A Hybrid Knowledge Graph and Bayesian Network Approach for Analyzing Supply Chain Resilience -- More power to SPARQL: From paths to trees -- Assessing Knowledge Graphs Accountability -- Reinforcement Learning-based SPARQL Join Ordering Optimizer -- SAP-KG: Synonym Predicate Analyzer across Multiple Knowledge Graphs -- Descriptive Comparison of Visual Ontology Change Summarisation Methods -- AgriNER: An NER Dataset of Agricultural Entities for the Semantic Web -- ClayBot: Increasing Human-Centricity in Conversational Recommender Systems -- Mining Symbolic Rules To Explain Lung Cancer Treatments -- GLENDA: Querying RDF Archives with full SPARQL -- Piloting topic-aware research impact assessment features in BIP! Services -- Explanation-based Tool for Helping Data Producers to Reduce Privacy Risks -- PathWays: entity-focused exploration of heterogeneous data graphs -- A Geological Case Study on Semantically Triggered Processes -- A System for Repairing EL Ontologies Using Weakening and Completing -- A User Interface Model for Digital Humanities Research: Case BookSampo - Finnish Fiction Literature on the Semantic Web -- Modeling Grammars with Knowledge Representation Methods: Subcategorization as a Test Case -- TRIC: A Triples Corrupter For Knowledge Graphs -- ExeKGLib: Knowledge Graphs-Empowered Machine Learning Analytics -- Hannotate: Flexible Annotation for Text Analytics from Anywhere -- Study-Buddy: A Knowledge Graph-Powered Learning Companion for School Students -- On the problem of automatically aligning indicators to SDGs -- Automating Benchmark Generation for Named Entity Recognition and Entity Linking -- VRKG-CollaborativeExploration - Thematic Data-driven Discussions via Knowledge Graphs on the Road of the Social Metaverse -- FOO: An Upper-Level Ontology for the Forest Observatory -- RoXi: a Framework for Reactive Reasoning -- SummaryGPT: Leveraging ChatGPT for Summarizing Knowledge Graphs -- Entity Typing with Triples using Language Models -- Industry -- Addressing the Scalability Bottleneck of Semantic Technologies at Bosch -- Knowledge Injection to Counter Large Language Model (LLM) -- Towards the deployment of Knowledge Based Systems in Safety Critical Systems Hallucination -- Towards the deployment of Knowledge Based Systems in Safety Critical Systems -- A Source-agnostic Platform for Finding and Exploring Ontologies at Bosch -- Wisdom of the Sellers: Mining Seller Data for eCommerce Knowledge Graph Generation -- Supplier Optimization at Bosch with Knowledge Graphs and Answer Set Programming -- Ontologies for Formalizing the Process of Configuring and Deploying Building Management Systems -- PhD Symposium -- Metaphor processing in the medical domain via Linked Data and Language Models -- Knowledge-based Multimodal Music Similarity -- Semantic Parsing for Knowledge Graph Question Answering with Large Language Models -- Semantic and Efficient Symbolic Learning over Knowledge Graphs -- Query answering over the polymorphic web of data -- Optimisation of Link Traversal Query Processing over Distributed Linked Data through Adaptive Techniques -- Formalizing Stream Reasoning for a Decentralized Semantic Web -- A Distributed and Parallel Processing Framework for Knowledge Graph OLAP -- Ontology-Compliant Knowledge Graphs -- Evaluating Knowledge Graphs with Hybrid Intelligence -- Exploiting Semantics for Explaining Link Prediction over Knowledge -- A Window into the Multiple Views of Linked Data.
Keywords: Information storage and retrieval systems; Data structures (Computer science).; Information theory; Database management; Application software; Artificial intelligence; Machine theory; Information Storage and Retrieval; Data Structures and Information Theory; Database Management; Computer and Information Systems Applications; Artificial Intelligence; Formal Languages and Automata Theory